“Aprendiendo en movimiento para el proceso de la interdisciplinaridad de los niños y niñas de segundo grado de educación básica, paralelo “a” de la Unidad Educativa del Milenio del cantón Penipe, provincia de Chimborazo, año lectivo 2015-2016” - Freire Orozco, Elvia Inés (2017)
The present research work helped to icnow, how learmng in movement contributes to the children's irrterésciphnary process. The objectives were to analyze the strategjes appüed in learmng in movement, demónstrate how imer-discipline takes place ín children's formation, and propose severa! activrties to enhance learmng in movement program for boys and girls. The methodology was desígned research, non-experimental it east without raanipulating the variables. The type of research was field research, since it was worked directly with stakeholders. in tfais case, the second gradéis. Descriprive methodology was used to detail the characteristics of the reality. Expiorative research helped to probé the unknown problem. Direct observation technique was appiied with an observation guide as its principal ínstrument for the twenty-four students to realize the problem presentad among them. As a conclusión, sport and game activities should be appiied in order to improve children's skills. Besides, they realize and respect the game rules, they were motivated io practice sport and avoid sedentarily life and improve physic and mental health.